Finite Element Multibody Simulation of a Breathing Crack in a Rotor with a Cohesive Zone Model. (13th March 2013) - Liong, Rugerri Toni; Proppe, Carsten
Abstract : The breathing mechanism of a transversely cracked shaft and its influence on a rotor system that appears due to shaft weight and inertia forces is studied. The presence of a crack reduces the stiffness of the rotor system and introduces a stiffness variation during the revolution of the shaft. Here, 3D finite element (FE) model and multibody simulation (MBS) are introduced to predict and to analyse the breathing mechanism on a transverse cracked shaft. It is based on a cohesive zone model (CZM) instead of linear-elastic fracture mechanics (LEFM). First, the elastic cracked shaft is modelled by 3D FE. As a second step, the 3D FE model of the shaft is transferred into an MBS model in order to analyze the dynamic loads, due to the crack, and the inertia force acting during rotation at different rotating speeds. Finally, the vibration responses in the centroid of the shaft obtained from MBS have been exported into FE model in order to observe the breathing mechanism. A bilinear crack closure model is proposed. The accuracy of the bilinear crack closure model and the solution techniques have been demonstrated by a comparison with the corresponding results of previous publications.